Numerical investigation of wing-propeller aerodynamic interaction through a vortex particle-based aerodynamic solver - Savino, A.; Cocco, A.; Zanotti, A.; Muscarello, V. (My University, 2022)
The present paper describes the results of a numerical investigation of a wing with an integrated propeller using the midfidelity aerodynamic solver DUST. The wing/propeller model considered in this work was widely investigated in literature both by experiments and high-fidelity CFD simulations and represents a classical benchmark case for the aerodynamic study of tiltrotors and electrical distributed propulsion aircraft configurations. The present numerical activity showed the capabilities of a mid-fidelity aerodynamic solver based on the vortex particle method, such as DUST, to capture the aerodynamic interactional effects of the installed propeller on the wing by a direct comparison of wing pressure coefficient distributions and propeller airloads with both experimental data and high-fidelity CFD simulations. Moreover, the instantaneous representation of the flow field between the propeller and the wing, as well as the pressure fluctuations on the wing surface, highlighted the capabilities to build a robust aerodynamic model of the wing/propeller in DUST aimed at studying the aeroacoustic aspects of such a complex configuration typical of Advanced Air Mobility aircraft configurations.